Prescott's microbiology - Willey, Joanne M. (McGraw-Hil, 2011)
"The themes of microbial evolution, ecology, and diversity continue to be integrated throughout the Eighth Edition. The most up-to-date information to maintain accurate descriptions of structures and processes, as well as provide exciting recent discoveries to illustrate essential points, has been added. Illustrations and photos feature three-dimensional renditions and bright, attractive colors! The art program also includes pedagogical features such as concept maps and annotation of key pathways and processes. Study aids have been developed to help students better understand the vast array of microbiology concepts."--Publisher's website.